Relationship between level of mental toughness and sport performance among UiTM Seremban Faculty of Sports Science and Recreation students / Dayang Rohani JM Abdul Maid - JM Abdul Maid, Dayang Rohani (2016)
This study was to identify the relationship between level of mental toughness and sports performance among UiTM Campus Seremban Faculty of Sports Science and Recreation (FSR) students. A survey used the questionnaire that is approach to 248 of FSR students. The respondents were chsen using the random sampling (systematic sampling). The instrument used consists of two sections of questionnaires which is demographic profile and Psychological Performance Inventory (PPI). This research addressed three main purposes, which are : (1) To identify the demographic profile among at UiTM Campus Seremban FSR students; (2) identify the differences types of sports of students on mental toughness; and (3) To determine the relationship between level of mental toughness and student's sports performance. This study utilized Descriptive analysis, Independent t-test and Pearson correlation. This study also found that demographic variables of: (1) gender; (2) age; (3) programme; (4) involvement in sport; (4) types of sports; (5) involvement in years; and (6) level of participation. For Psychological Performance inventory that are consists 42 question and involved 7 factors which are: (I) self confidence; (2) negative energy control; (3) attention control; (4) visualization or imagery control; (5) motivation; (6) positive energy; and (7) attitude control.